A coupled ionosphere‐raytrace model for high‐power HF heating. Issue 22 (23rd November 2015) - Zawdie, K. A.; Huba, J. D.; Drob, D. P.; Bernhardt, P. A.
Abstract: The first 3‐D model of artificial HF ionospheric heating to self‐consistently calculate the modification in heating location due to evolving ionospheric gradients has been developed. The model combines the ionosphere model SAMI3/ESF and the HF propagation code MoJo‐15. At each time step, the simulated path of the HF wave through the ionosphere is used to determine the HF heating location. These calculations have been used to explain the physical mechanism responsible for the snapback effect observed in an Arecibo HF heating experiment described by Bernhardt et al. (1988). The heater wave is refracted by the density cavity, which causes the heating location to drift in longitude. Eventually, the density cavity convects into the path of the refracted ray, such that only a small portion of the ray is above the threshold for HF heating and the heating location snaps back even though the ray itself is still refracted in longitude. Key Points: The first self‐consistent 3‐D model of artificial HF heating has been developed The simulations explain the physical mechanism responsible for the snapback effect The snapback effect can be suppressed by reducing the heater power and/or frequency